Unraveling low nucleation temperatures in pool boiling through fluctuating hydrodynamics simulations. (September 2020) - Magaletti, Francesco; Georgoulas, Anastasios; Marengo, Marco
Highlights: We studied the boiling inception on a hot surface through Fluctuating Diffuse Interface simulations. This novel technique captures the spontaneous nucleation of vapor bubbles thanks to the proper description of thermal fluctuations at mesoscale. We found that bubble-bubble interaction and coalescence enhances the lifetime of smaller vapor embryos, and increases the probability of local evaporation, thus reducing the boiling onset temperature. We observed a non-homogeneous distribution of nucleation sites on the hot surface, again enhancing the bubble coalescence. Abstract: When dealing with numerical simulations of boiling phenomena, the spontaneous appearance of vapor bubbles is one of the most critical feature to be addressed. Capturing bubble formation during the dynamics, instead of patching vapor regions as initial conditions, is crucial for the correct evaluation of nucleation rates and nucleation site density, two of the most important parameters characterizing boiling. In this work the Diffuse Interface modeling for vapor–liquid systems is coupled with Fluctuating Hydrodynamics Theory to properly address this aspect and to analyze the detailed nucleation mechanism during boiling inception on a hot surface. The simulations revealed a new enhancing mechanism of bubble formation that is able to explain the low onset temperature measured in boiling experiments on ultra-smooth, wettable surfaces: the interaction and coalescence between sub-critical vapor embryos plays a fundamental role in lowering the onset temperature, increasing the lifetime of the embryos and their probability to trigger the phase change.